TEACHING VOCABULARY ON CONCRETE NOUN THROUGH CROSSWORD PUZZLE - Rahmayanti, Ririn; ., Sudarsono; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of this research is to find out the level of the effectiveness of using crossword puzzle to enrich the vocabulary of Year-8 students of â€œSMPN 16 Pontianakâ€ in Academic Year 2014/2015. This research was a pre-experimental study. The sample was a purposive sampling, that is, Class VIII E that consists of 36 students. The data were collected from the pre-test and post-test. The data were analyzed by using Effect Size (ES) formula. The research finding shows that the effect size of the treatment is 1.27 (> 1.00). It is categorized â€œstrongâ€. It indicates that crossword puzzle is very effective to teach vocabulary to Year-8 students. Key words: crossword puzzle, teaching vocabulary Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat efektifitas dari crossword puzzle untuk memperkaya kosa kata siswa kelas 8 SMPN 16 Pontianak tahun ajaran 2014/2015. Penelitian ini adalah sebuah penelitian pre-experimental. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Sampel dalam penelitian ini adalah siswa kelas VIII E yg terdiri atas 36 siswa. Data-data di ambil dengan menerapkan rumus ES (tingkat efektifitas). Hasil penelitian menunjukkan bahwa tingkat efektifitas dari penggunaan crossword puzzle adalah 1.27 (> 1.00). Hasil ini dikategorikan memiliki efek yang kuat. Hal ini menunjukkan bahwa crossword puzzle sangat efektif utuk mengajarkan kosa kata kepada siswa kelas 8. Kata kunci: crossword puzzle, mengajarkan vocabulary